Optimization of Bhabinkamtibmas Performance to Prevent Theft in the Batang Police Station Area (Advances in Police Science Research Journal, 2024)
Optimization of Bhabinkamtibmas Performance in the Batang Police Station area to prevent theft is needed. Bhabinkamtibmas is the vanguard of police functions in harkamtibmas in the community. The performance of Bhabinkamtibmas is influenced by the competence and facilities and infrastructure owned by Bhabinkamtibmas. The competence of Bhabinkamtibmas consists of aspects of quantity and quality. The quantity aspect consists of the number of Bhabinkamtibmas serving in a region. While from the aspect of quality consists of knowledge, skills and behavioral attitudes. This research presents the stages of the report in the form of initial conditions, expected conditions and problem solving based on relevant concepts and theories. From this stage, researchers found several shortcomings, including most members of Bhabinkamtibmas have not attended Bhabinkamtibmas development education and the facilities and infrastructure owned by Bhabinkamtibmas are still lacking to support the performance of Bhabinkamtibmas to prevent theft. Researchers provide recommendations as suggestions for problem solving by providing opportunities for Bhabinkamtibmas members to continue their education and FGD (Forum Group Discussion), as well as collaborating with side agencies by utilizing CSR (Corporate Social Responsibility).
Keywords: Kinerja, Kompetensi, Sarana dan Prasarana